2022
DOI: 10.3389/fped.2022.854519
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Phenotype-vs. Genotype-Guided Therapy Based on Clarithromycin Resistance for Helicobacter pylori Infection in Children

Abstract: BackgroundClarithromycin resistance reduces the eradication rate of Helicobacter pylori (H. pylori). Cultures with susceptibility testing and molecular determination of genotypes are recommended to guide-tailored therapy.MethodsWe retrospectively enrolled patients aged 6 and 18 years with H. pylori infection, who underwent an endoscopy and agreed to undergo both culture and genetic testing for clarithromycin resistance. Patients receiving tailored therapy based on traditional culture results (phenotype-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Nevertheless, molecular techniques are increasingly used due to the culture’s time-consuming and fastidious nature [ 82 ]. Feng et al found that the success of tailored therapy based on clarithromycin susceptibility is significantly higher when employing the molecular detection of point mutations (92%) in comparison to the phenotypic method (70.4%) [ 83 ].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Nevertheless, molecular techniques are increasingly used due to the culture’s time-consuming and fastidious nature [ 82 ]. Feng et al found that the success of tailored therapy based on clarithromycin susceptibility is significantly higher when employing the molecular detection of point mutations (92%) in comparison to the phenotypic method (70.4%) [ 83 ].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%